RECENT HISTORY OF UZBEKISTAN AS A GLOBAL HISTORICAL PROCESS (American Journal of Pedagogical and Educational Research, 2024)
In the article, the national statehood of Uzbekistan, the modern history of the new Uzbekistan, modern history, the formation of deep knowledge about the history of the country among modern youth, the formation of views on the reforms of the history of Uzbekistan during the period of independence, the main stages of development of the Republic of Uzbekistan, the foreign policy of the Republic of Uzbekistan, the right questions, such as large-scale democratic reforms, the ideal image of the new Uzbekistan in accordance with the information process were highlighted by globalization, as well as significant work to create a new media image.